Storying energy consumption: Collective video storytelling in energy efficiency social marketing. (1st May 2018) - Gordon, Ross; Waitt, Gordon; Cooper, Paul; Butler, Katherine
Abstract: Despite calls for more socio-technical research on energy, there is little practical advice to how narratives collected through qualitative research may be melded with technical knowledge from the physical sciences such as engineering and then applied in energy efficiency social action strategies. This is despite established knowledge in the environmental management literature about domestic energy use regarding the utility of social practice theory and narrative framings that socialise everyday consumption. Storytelling is positioned in this paper both as a focus for socio-technical energy research, and as one potential practical tool that can arguably enhance energy efficiency interventions. We draw upon the literature on everyday social practices, and storytelling, to present our framework called 'collective video storytelling' that combines scientific and lay knowledge about domestic energy use to offer a practical tool for energy efficiency management. Collective video storytelling is discussed in the context of Energy+Illawarra, a 3-year cross-disciplinary collaboration between social marketers, human geographers, and engineers to target energy behavioural change within older low-income households in regional NSW, Australia. Highlights: We contribute to debate about socio-technical perspectives, and use of narrative in environmental management. We show how lay and technical narratives can be re-told in energy efficiency social marketing. We provide a methodological framework we term collective video storytelling. We argue collective video storytelling can play an important part in environmental management programmes.